Manfaat Latihan Kekuatan Otot terhadap Kadar HbA1c pada Orang Dewasa dengan Prediabetes: Laporan Kasus Berbasis Bukti - Simanjuntak, Owen Paruhum; Lubis, Anna Mira (Jurnal Penyakit Dalam Indonesia, 2026)
Prediabetes is a metabolic condition of impaired glucose homeostasis which results in elevated blood glucose levels. Besides the higher risk of developing diabetes, prediabetes is associated with increased risk of cancer, dementia, heart failures, and coronary artery disease. The common first line treatment regimen given to this group are healthy diet and aerobic exercise. However, some conditions might prevent patients from doing aerobic exercises therefore there is a need for alternatives. This evidence-based case report aims to evaluate the benefit of resistance training on HbA1c levels compared to control group (no exercise) in prediabetic adults. Literature search was conducted across several databases (PubMed, Cochrane, Scopus, and Wiley). Included articles are then critically appraised with the Oxford Center for Evidence-Based Medicine (CEBM) tool. Levels of evidence for each included study are assessed with the Oxford CEBM 2011 levels of evidence table.  Out of 658 studies screened, 15 studies were selected and 2 were included. A systematic review and meta-analysis found that resistance training with low-to-moderate load resulted in a significant reduction of HbA1c compared to the control group. A randomized controlled trial (RCT) also found significant reduction in HbA1c levels after 12 and 24 months of resistance training, compared to the control group. However, study found that resistance training with high load does not significantly reduce HbA1c levels. Current evidence supports the regimen of low-to-moderate resistance training (performed three times per week for 50-60 minutes per session at an intensity of 50-75% of one-repetition maximum) to lower HbA1c levels in adult prediabetic populations.